(untitled) (International Journal of Food and Nutritional Sciences, 2025)
Education is one of the most powerful tools for effecting change in the world and unlocking success across various fields. It expands one’s worldview and forms the foundation for all our abilities. Children, as the most valuable resource and hope for the future, are born with innate fearlessness and curiosity about their surroundings. It is essential to nurture children carefully to help them realize their potential, establish strong emotional connections with their environment, and develop into physically, psychologically, and socially healthy adults. This paper aims to evaluate the amenities and services provided at Anganwadi Centres (AWCs) in accordance with the standards set by the Integrated Child Development Service (ICDS) system, focusing on young children aged 0–6 years. It is crucial to determine whether the Anganwadi Centres are effectively fulfilling their responsibilities. The effectiveness of the Integrated Child Development Services program in addressing childhood issues is also assessed. The paper examines the educational and nutritional programs offered to children aged 0 to 6 years at Anganwadi centres (AWCs). The study analyses various perspectives on early childhood and presents a range of theoretical, scientific, and policy issues. Additionally, it summarizes key debates in Early Childhood Care and Education (ECCE). The author emphasizes the needs of the child and proposes measures and potential solutions to enhance the quality of learning and improve learning outcomes for children participating in ECCE programs